III [compact disc] - Kondratenko, Oleg, 1973- (Dualtone Music Group, 2019)
Two-time Grammy-nominated band, The Lumineers, are back with their third album, a cinematic piece presented as a narrative in three chapters, with each one centering on one main character. Decidedly darker than their previous work in concept, but replete with their trademark expressive vocals and dynamic arrangements, it boldly and expertly goes in an artistic direction not yet traveled by the band.